LEGAL GYMNASTICS: AN EVALUATION OF THE JUDGMENT IN Z v Z [2022] ZASCA 113 - Arthur van Coller; Ebrezia Johnson (Obiter, 2023)
The South African Supreme Court of Appeal (SCA) recently considered an appeal (Z v Z [2022] ZASCA 113) against an order of the Eastern Cape Division of the High Court, Port Elizabeth (ECD). The ECD upheld a special plea and confirmed that a parent lacks locus standi in judicio to claim maintenance from the other parent, for and on behalf of adult dependent children, during divorce proceedings (Z v Z supra par 2). The SCA, however, reasoned that the obligations of a divorce court set out in section 6 of the Divorce Act (70 of 1970) (the Act) by implication made provision for a parent to apply on behalf of an adult child for maintenance. The SCA, accordingly, dismissed the special plea and the appeal was upheld with costs. The SCA judgment is noteworthy as several previous High Court judgments found that adult dependent children must pursue claims for maintenance against their parents in their own name. Interestingly, most courts of first instance have reasoned that adult dependent children should be before the court when applying for maintenance. However, the SCA did not share the same position. In its reasoning, the SCA emphasised convenience and stressed that all the matters relevant to the divorce, including maintenance of dependent children, should and could be disposed of at the hearing of the main action. The SCA confirmed that both parents have a duty to maintain their dependent children and that this duty, at times, persists after the child attains majority age. The SCA further commented that children, including adult children, should be removed from the conflict between the divorcing parents as far as possible. The SCA, therefore, held that the requirements of section 6 of the Act provide the basis for admitting a claim by a parent for maintenance for and on behalf of an adult dependent child. It is submitted that the reasoning of the SCA and the precedent created could undermine the ability of a court to make an order of parental support for adult dependent children, and may ultimately result in outcomes that do not effectively provide for the needs of the adult child. This case note evaluates the facts of the matter together with the reasoning of the High Court and the SCA. The previous judgments on parents representing their adult dependent children during divorce proceedings are then evaluated. The specific intent of the case note is to establish whether section 6 of the Act confers locus standi on a parent to apply for maintenance for and on behalf of their adult dependent children during divorce proceedings. The benefits and challenges of conferring locus standi on parents of adult children are also considered. The last relevant issue that is evaluated, and on which the courts did not have to adjudicate, relates to the termination of a parent’s duty to provide financial support for their adult children. This case note ultimately aims to establish what obligations and powers are inherent in the application of section 6 of the Act and what procedures may, therefore, be employed by a Divorce Court when an adult dependent child applies for parental support.